Teacher Oral Corrective Feedback In Video Conference Applications For Online Learning - Anugrah, Yuda; Friatin, Lilies Youlia; Sugiarto, Bambang Ruby (Wahana Pendidikan, 2024)
This qualitative case study investigates the strategies employed by teachers to provide oral corrective feedback during online learning sessions via video conferencing applications and identifies the challenges encountered in this process. Data were gathered through observations and semi-structured interviews with one English teacher and four tenth-grade students from a Vocational High School in Tasikmalaya. The study addresses the central issue of delivering effective oral corrective feedback in an online learning environment. The findings indicate that teachers utilize various feedback types, such as recast, explicit correction, and repetition. Nevertheless, challenges like poor internet connectivity and technical disruptions hinder the communication and feedback process. This study highlights the complexities involved in delivering oral corrective feedback online and underscores the need to address technical obstacles to improve feedback efficacy.